A imagem enquanto corpo de um tempo - Amanda Ehrhardt Cherici Nogueira (2022)
This research seeks to build an understanding of the experimental and procedural nature of photography, considering the image as a stretch in time. Therefore, it explores the time-photography relationship from the suspicion that time could be a plastic element for photography. It focuses on different processes, uses, technical and aesthetic possibilities of the photographic device, exploring the sociopolitical context in which they emerge and intend and their connections with other languages and domains of knowledge. It explores the time-photography relationship, from its plasticity and expressive power, including narrative and mathematics. Among the informational and analytical searches, contextualized results are considered and arranged within the temporal count. Thus, it extends from the pioneering processes to contemporary art, bringing together authors, images and paradigmatic events that assemble the narrative of the history of photography, establishing new relationships, in dialogue with the urges of its time and those of the present time.